'Reducing Delays In Vaccination' (REDIVAC) trial: a protocol for a randomised controlled trial of a web-based, individually tailored, educational intervention to improve timeliness of infant vaccination. Issue 5 (22nd May 2019) - Dempsey, Amanda F; Wagner, Nicole; Narwaney, Komal; Pyrzanowski, Jennifer; Kwan, Bethany M; Kraus, Courtney; Gleason, Kathy; Resnicow, Ken; Sevick, Carter; Cataldi, Jessica; Brewer, Sarah E; Glanz, Jason M
Abstract : Introduction: Increasing numbers of children are failing to receive many recommended vaccines, which has led to significant outbreaks of vaccine-preventable diseases in the USA and worldwide. A major driver of undervaccination is parental vaccine hesitance. Prior research demonstrates that mothers are the primary decision maker for infant vaccination, and that their vaccination attitudes form primarily during pregnancy and early in their infant's life. Methods and analysis: This manuscript describes the protocol for an ongoing three-armed randomised controlled trial done at Kaiser Permanente Colorado (KPCO). The trial aims to test the efficacy of provided tailored, individualised information via the Internet to pregnant and new mothers versus untailored information versus usual care on the timeliness of infant vaccination. The primary outcome to be assessed is vaccination status, which is a dichotomous outcome (up to date vs not) assessed at age 200 days, reflecting the time when infants should have completed the first set of vaccine provided (at age 2, 4 and 6 months). Infants with one or more age-appropriate recommended vaccines at least 30 days delayed are categorised as not up to date whereas all other infants are considered up to date. Secondary outcomes include vaccination status at age 489 days, reflecting receipt of recommended vaccines at age 12–15 months, as well as vaccination attitudes, hesitancy and intention. Vaccination data will be derived from the electronic medical record and the state immunisation registry. Other secondary outcomes will be assessed by online surveys. Ethics and dissemination: The study activities were approved by the Institutional Review Boards of the University of Colorado, KPCO and the University of Michigan. Results will be disseminated through peer-reviewed manuscripts and conference presentations. Trial registration number: NCT02665013 ; Pre-results.